INFLUENCE OF BIOZYME ON GROWTH, YIELD AND QUALITY OF ONION (ALLIUM CEPAL.) CV. SUKHSAGAR - S. DE; D. MANNA; A. SARKAR; T.K. MAITY (The Bioscan, 2013)
Field experiment was conducted to study the influence of Biozyme on growth, yield and quality of onion. Application of Biozyme with or without fertilizer had significant effect on different growth and yield attributing characters like plant height, number of roots per plant, diameter of bulb and bulb weight as well as yield. Maximum total yield (31.89 t/ha) with marketable yield (31.27 t/ha) was obtained when the crop was treated withsoil application of recommended dose of fertilizer (125:80:100) + seedling treatment with Biozyme Seed plus (@ 10 mL/l water) + Biozyme Veg. granules (@ 20 kg/ha) + Biozyme Veg. liquid (@ 500 mL/ha). The quality attributes like Pyruvic acid (4.45 μ mol/g) and Total soluble solid (13.95°B) were markedly influenced by the application of Biozyme. Bulbs obtained from different treatment had edge over control in in relation to shelf life. An economic analysis revealed that application of Biozyme was more beneficial over control. The results led to the conclusion that for better growth, yield and quality of onion with higher economic return of the crop may be treated with soil application of recommended dose of fertilizer (125:80:100) + seedling treatment with Biozyme Seed plus (@ 10 mL/l water) + Biozyme Veg. granules (@ 20 kg/ha) + Biozyme Veg. liquid (@ 500 ml/ha), in the plains of New Alluvial Zone of West Bengal.